Neonatal Pain, Opioid, and Anesthetic Exposure; What Remains in the Human Brain After the Wheels of Time? - van den Bosch, Gerbrich E.; Tibboel, Dick; de Graaff, Jurgen C.; El Marroun, Hanan; van der Lugt, Aad; White, Tonya; van Dijk, Monique (Frontiers in Pediatrics, 2022)
OBJECTIVE: To evaluate possible negative long-term effects of neonatal exposure to pain, opioids and anesthetics in children and adolescents. STUDY DESIGN: We studied five unique groups of children recruited from well-documented neonatal cohorts with a history of neonatal exposure to pain, opioids or anesthetics at different points along the continuum from no pain to intense pain and from no opioid exposure to very high opioid exposure in the presence or absence of anesthetics. We evaluated children who underwent major surgery (group 1 and 2), extracorporeal membrane oxygenation (group 3), preterm birth (group 4) and prenatal opioid exposure (group 5) in comparison to healthy controls. Neuropsychological functioning, thermal detection and pain thresholds and high-resolution structural and task-based functional magnetic resonance imaging during pain were assessed. In total 94 cases were included and compared to their own control groups. RESULTS: Children and adolescents in groups 3 and 5 showed worse neuropsychological functioning after high opioid exposure. A thicker cortex was found in group 1 (pain, opioid and anesthetic exposure) in only the left rostral-middle-frontal-cortex compared to controls. We found no differences in other brain volumes, pain thresholds or brain activity during pain in pain related brain regions between the other groups and their controls. CONCLUSIONS: No major effects of neonatal pain, opioid or anesthetic exposure were observed in humans 8-19 years after exposure in early life, apart from neuropsychological effects in the groups with the highest opioid exposure that warrants further investigation. Studies with larger sample sizes are needed to confirm our findings and test for less pronounced differences between exposed and unexposed children.